PERSEPSI TERHADAP PEMBERITAAN FENOMENA FETISH DI MEDIA MASSA ONLINE - Lulu Annizha Anwar; Zelfia Zelfia; Abd Majid (UNIVERSITAS MUSLIM INDONESIA, 2020)
Fetishes include dependence on inanimate objects to induce sexual arousal. At the end of July 2020, the jarik cloth fetish phenomenon occurred in Indonesia, which was widely reported through the mass media, both online mass media and social media. The purpose of this study was to determine of the perception of Communication Studies students at the Muslim University of Indonesia on the reporting of the fetish phenomenon in online mass media and how attitude of Communication Studies students at the Muslim University of Indonesia in responding to the news of fetish phenomenon in online mass media. This study uses qualitative research methods by trying to collect data or information related to the perception of reporting on the fetish phenomenon in online mass media. This study was conducted by collecting data through interviews, documentation, and literature study. This study was conducted for one month in the Communication Studies Program, Faculty of Letters and Communication Studies, Muslim University of Indonesia, Makassar City. The result of this study indicated that the perception of the Communication Studies students at the Muslim University of Indonesia on the reporting of the fetish phenomenon in online mass media is different, but some are almost the same depending on the perspective of each individual. Most students have a positive perception of the news. Based on cognitive aspects, affective aspects, and psychomotor aspects, changes in thought patterns and actions occur after knowing the news of fetish phenomenon in online mass media. Because the perception of Communication Studies students at the Muslim University of Indonesia is different, but some are almost the same, so that the attitude of students in responding to the news of the fetish phenomenon in online mass media is also different and some are almost the same